2015
DOI: 10.5507/bp.2012.104
|View full text |Cite
|
Sign up to set email alerts
|

Detection of nano- and micro-sized particles in routine biopsy material - pilot study

Abstract: Background. Nanotechnology is receiving enormous funding. Very little however is known about the health dangers of this technology so far. Chronic tonsillitis is one of a number of diseases called idiopathic. Among other factors, the tonsils are exposed to suspended particles in inhaled air including nano particles. The objective of this study was to detect and evaluate metallic particles in human tonsil tissue diagnosed with chronic tonsillitis and in amniotic fluid as a comparison. Methods. Scanning electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Iron-based MPs and NPs of exogenous origin have also been previously found in tissue samples by Raman microspectroscopy [ 6 , 8 , 16 ]. Iron oxide dust and fumes are known to cause harm to respiratory tract (pneumosiderosis) which has been documented in welders occupationally exposed to welding fumes and are also emitted by fossil fuel combustion into the environment [ 6 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Iron-based MPs and NPs of exogenous origin have also been previously found in tissue samples by Raman microspectroscopy [ 6 , 8 , 16 ]. Iron oxide dust and fumes are known to cause harm to respiratory tract (pneumosiderosis) which has been documented in welders occupationally exposed to welding fumes and are also emitted by fossil fuel combustion into the environment [ 6 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their extremely small scale, the relative surface of NPs is larger and thus the number of reactive atom groups on their surface is several times higher than in MPs and larger particles [ 4 ]. They also exhibit increased diffusivity and delayed sedimentation—therefore, they tend to stay airborne in the atmosphere for longer periods of time than MPs, which increases the risk of their inhalation [ 5 , 6 ]. They are ubiquitous in the environment, composed mostly of metal oxides and carbon, predominantly of antropogenous origin—produced, for example, by smoking, fossil fuel combustion, welding or road traffic [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In audiology, nanotechnology research has shown promise in developing advanced sound and hearing implants, offering a potential breakthrough for individuals with profound deafness [ 189 ]. Moreover, the presence of metallic particles in human tonsil tissue and amniotic fluid has raised intriguing possibilities regarding their role in disease causation and emerging nanopathology [ 190 ].…”
Section: Other Pediatric Applicationsmentioning
confidence: 99%
“…[189] Chronic tonsillitis and other diseases Metallic particles in human tonsil tissue and amniotic fluid could help to point towards alternative causes of some diseases and emerging nanopathology. [190] Exposure to nanoparticles Nano-enabled consumer products-resuspension rates of particles vary depending on the product, flooring, and resuspension force. Products containing Cu, Ag, and Zn nanomaterials had higher rates.…”
Section: Disease/conditionmentioning
confidence: 99%